Altered Antibody Response to Epstein-Barr Virus in Patients With Rheumatoid Arthritis and Healthy Subjects Predisposed to the Disease. A Twin Study - Svendsen, Anders J.; Westergaard, Marie Christine Wulff; Draborg, Anette Holck; Holst, René; Kyvik, Kirsten O.; Jakobsen, Marianne A.; Junker, Peter; Houen, Gunnar (Frontiers in Immunology, 2021)
Objectives: To study Epstein-Barr virus (EBV) antibody patterns in twin individuals with rheumatoid arthritis (RA) and their healthy co-twins, and to determine the heritability of antibody responses against the EBV encoded EBNA1 protein. Methods: Isotypes of EBNA1 antibodies were measured in 137 RA affected- and 150 healthy twin pairs. We estimated the effect of RA and RA predisposition, anti-citrullinated antibodies (ACPA), IgM rheumatoid factor (RF), the shared epitope (SE) and the PTPN22-T allele (PTPN22) on the level of EBNA1 antibodies. We also determined the heritability of EBNA1 antibody levels. Results: IgA-EBNA1 antibody levels were increased in twins from RA discordant twin pairs irrespective of RA, ACPA or IgM-RF status. The IgG-EBNA1 antibody level was elevated in healthy co-twins from RA discordant twin pairs but not in RA affected twins. The IgM-EBNA1 antibody level was elevated in both RA twins and their healthy co-twins. The effect of RA on the IgA-EBNA1 antibody level was reversed when SE was present and with no effect of PTPN22. The heritability of IgA-, IgG- and IgM-EBNA1 antibody level was 40.6 %, 65.5% and 54.3%, with no effect of environment shared by the twins. Conclusion: EBNA1 antibody levels are distinctively different between patients with RA and healthy subjects but also between relatives of RA strongly predisposed to RA and healthy subjects. The high level of IgA EBNA1 antibodies associated with RA and a family predisposition to RA is attributable to both genetics incl. the shared epitope and environmental variation.